ADL and IADL in Community-Living Elderly using long-term Home-Visit Rehabilitation - Furuta, Daiju; Katai, Satoshi; Ono, Chie; Ikegami, Shota; Ishida, Yuzu; Horiuchi, Hiroshi (Journal of Japanese Association for Home Care Medicine, 2023)
Background: The number of elderly people requiring home-visit rehabilitation is increasing every year. There is a need to improve the quality of home-visit rehabilitation and to work toward independence.Objective: To understand the current status of home-visit rehabilitation for elderly people living in a community, and to examine effective rehabilitation interventions.Methods: 332 subjects who use long-term home-visit rehabilitation were included in the study, and their basic information and changes in ADL (Barthel Index) and IADL (Frenchay Activities Index) over a one-year period were investigated.Results: Overall BI was significantly decreased and FAI showed significant improvement (correlation coefficient : 0.25). In the cerebrovascular and fracture groups, BI remained unchanged and FAI improved. In the internal disorders and neuromuscular disease groups, BI decreased significantly but FAI was maintained.Conclusions: ADL and IADL do not necessarily correlate in long-term home-visit rehabilitation users over a 1-year period. In addition, changes in ADL and IADL were characterized differently for each disease. It is important to provide comprehensive intervention to improve the performance of daily life activities in home-visit rehabilitation, focusing on IADL and based on the characteristics of the disease.